Edible Mushrooms: A Comprehensive Review on Bioactive Compounds with Health Benefits and Processing Aspects - Kumar, Krishan (2021)
Mushrooms are well-known functional foods due to the presence of a huge quantity of nutraceutical components. These are well recognized for their nutritional importance such as high protein, low fat, and low energy contents. These are rich in minerals such as iron, phosphorus, as well as in vitamins like riboﬂavin, thiamine, ergosterol, niacin, and ascorbic acid. They also contain bioactive constituents like secondary metabolites (terpenoids, acids, alkaloids, sesquiterpenes, polyphenolic compounds, lactones, sterols, nucleotide analogues, vitamins, and metal chelating agents) and polysaccharides chieﬂy β-glucans and glycoproteins. Due to the occurrence of biologically active substances, mushrooms can serve as hepatoprotective, immune-potentiating, anti-cancer, anti-viral, and hypocholesterolemic agents. They have great potential to prevent cardiovascular diseases due to their low fat and high ﬁber contents, as well as being foremost sources of natural antioxidants useful in reducing oxidative damages. However, mushrooms remained underutilized, despite their wide nutritional and bioactive potential. Novel green techniques are being explored for the extraction of bioactive components from edible mushrooms. The current review is intended to deliberate the nutraceutical potential of mushrooms, therapeutic properties, bioactive compounds, health beneﬁts, and processing aspects of edible mushrooms for maintenance, and promotion of a healthy lifestyle.